2014
DOI: 10.1007/s00204-014-1310-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetic modeling of hydrogen cyanide levels in human breath

Abstract: Hydrogen cyanide (HCN) is a potent and fast-acting toxin increasingly recognized as an important cause of death in fire victims. Prompt diagnosis and treatment of cyanide poisoning are essential to avoid fatalities. Unfortunately, there are at present few rapid diagnostic methods. A noninvasive methodology would be to use HCN in exhaled air as a marker for systemic exposure. To explore this possibility, we developed a preliminary physiologically based pharmacokinetic model. The model suggests that breath HCN l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…With regard to hydrogen cyanide in particular, the elimination half-life in exhaled air for humans was 15.6 ± 3.9 min (Stamyr et al, 2008), similar to the rat blood cyanide half-life reported by Leuschner et al (1991), suggesting the impact of ''gaps'' of toxicokinetics might be similar. Stamyr et al (2014) recently used physiologically based pharmacokinetic modeling of HCN lethality from human case reports with times to death ranging from $7 to 60 min to derive a toxic load exponent of 2.4. This human value is slightly higher than the value of 1.6 for rats (derived herein) and the value of 2.1 for monkeys derived by the National Research Council (2002).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to hydrogen cyanide in particular, the elimination half-life in exhaled air for humans was 15.6 ± 3.9 min (Stamyr et al, 2008), similar to the rat blood cyanide half-life reported by Leuschner et al (1991), suggesting the impact of ''gaps'' of toxicokinetics might be similar. Stamyr et al (2014) recently used physiologically based pharmacokinetic modeling of HCN lethality from human case reports with times to death ranging from $7 to 60 min to derive a toxic load exponent of 2.4. This human value is slightly higher than the value of 1.6 for rats (derived herein) and the value of 2.1 for monkeys derived by the National Research Council (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples are ingestion of volatile foods or substances (Beauchamp et al 2010;Traucher et al 1996), breath diagnosis of life-threatening hydrogen cyanide (HCN) toxicity in victims of fire (Stamyr et al 2015), alcohol and ethylene glycol poisoning (Johanson 2000;Walsh and Macleod 1983;Eder et al 1998), carbon monoxide exposures (Cunnington and Hormbrey 2002), and toluene abuse (Garriott et al 1981).…”
Section: Toxicokineticsmentioning
confidence: 99%
“…First, pharmacokinetic modelling can be improved by intravital imaging. PBPK modelling is of high relevance for simulation of compound concentrations in blood or organs (Golubovskaya et al, 2015[9]; Stamyr et al, 2015[20]; Widera, 2015[24]; Ghallab, 2015[5]) as well as for interspecies extrapolation (Thiel et al, 2015[21]). However, current PBPK models consider individual organs as single compartments (Schug et al, 2013[19]; Mielke et al, 2011[14]).…”
Section: mentioning
confidence: 99%